Teaching environmental health to children an interdisciplinary approach - Hursh, David W. 1948-; Martina, Camille; Trush, Michael; Davis, Hillary; Davis, Hillary B. (Dordrecht New York Springer, 2011)
Every day we are exposed to toxins and toxicants that can impact our health.  Yet we rarely teach elementary and secondary students about these exposures and how they can reduce their risk to them.  In this book we highlight activities and curriculum developed at nine universities in the United States from a grant funded by the National Institute of Environmental Health Sciences.  Our goal is to extend these lessons to a global audience and for classroom teachers of all subjects and age levels to include environmental health in their teaching.  ?An invaluable tool for equipping informed citizens to think about the environment and its human impacts --both the science, and equally important, the social and ethical dimensions? , Howard Frumkin, M.D., Dr. P.H., Dean, School of Public Health, University of Washington, Seattle, WA, US
Electronic reproduction.
Keywords: Environmental health -- Study and teaching; Health education